2021
DOI: 10.1159/000521306
|View full text |Cite
|
Sign up to set email alerts
|

Protector Role of Intraocular Lenses under Artificial Light Conditions

Abstract: Introduction: The aim of this work is to analyse, in an in vitro model, the possible protective effects of ultraviolet- (UV-) or UV/ blue-filtering intraocular lens (IOLs) under LED lighting conditions. Methods: 10 models of IOLs were evaluated. Light transmission spectrum was recorded from 300 to 800 nm, in steps of 1 nm. Photodamage in vitro model was induced in ARPE-19 cells by blue LED light (465-475 nm). Changes in cell viability and oxidative stress variables were studied to assess the protective effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…[60][61][62] Another study in ARPE-19 cells, however, reported that BLF IOLs did not reduce the expression of heme oxygenase-1 or have a protective effect on mitochondrial membrane potential in these experiments, although blue LED light exposure led to increased oxidative stress (measured by heme oxygenase-1 levels). 63 The results of these in vitro studies confirm that blue light can cause damage to RPE cells. Some of the studies supported the protective function of BLF IOLs, [60][61][62] but others did not report significant effects with BLF, 63 possibly because of variations in study design and assessments.…”
Section: Protective Role Of Blue Light Filters: In Vitro Studiesmentioning
confidence: 56%
See 2 more Smart Citations
“…[60][61][62] Another study in ARPE-19 cells, however, reported that BLF IOLs did not reduce the expression of heme oxygenase-1 or have a protective effect on mitochondrial membrane potential in these experiments, although blue LED light exposure led to increased oxidative stress (measured by heme oxygenase-1 levels). 63 The results of these in vitro studies confirm that blue light can cause damage to RPE cells. Some of the studies supported the protective function of BLF IOLs, [60][61][62] but others did not report significant effects with BLF, 63 possibly because of variations in study design and assessments.…”
Section: Protective Role Of Blue Light Filters: In Vitro Studiesmentioning
confidence: 56%
“… 60–62 Another study in ARPE-19 cells, however, reported that BLF IOLs did not reduce the expression of heme oxygenase-1 or have a protective effect on mitochondrial membrane potential in these experiments, although blue LED light exposure led to increased oxidative stress (measured by heme oxygenase-1 levels). 63 …”
Section: Blue Light Filtration Ocular Health and Systemic Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…), as halo perception and other dysphotopsias are one of the main postoperative complaints www.nature.com/scientificreports/ of these patients 12,69,70 and some multifocal IOLs can influence spatio-chromatic vision 71 . There is also a growing research interest in the effect of blue-light filtering intraocular lenses 72,73 and optimizing new refractive surgery techniques to minimize positive dysphotopsias.…”
Section: Discussionmentioning
confidence: 99%